2006
DOI: 10.1039/b417154n
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescent phosphors

Abstract: This review outlines the general properties of cathodoluminescent phosphors, especially of ZnS : Ag : Cl (blue), ZnS : Cu : Al (green) and Y 2 O 2 S : Eu (red). These phosphors, having an average particle size of 4 mm, are particularly important in the production of full-color cathodoluminescence display devices such as cathode ray tubes. The growth mechanism of ZnS phosphors with fluxes is also discussed on the basis of recent study. It is emphasized that screenable phosphor particles with chemically clean su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Generally, most phosphors are prepared by conventional solidstate process, and the resulted samples contain irregular shape, broad size distribution. The appearance of new technology and new application, such as the ink-jet, plasma display panel (PDP) and field emission displays (FED), has brought higher demand for phosphor [1][2][3]. It has been reported that phosphor must have fine size, narrow size distribution, non-agglomeration mono-disperse spherical morphology for excellent luminescent properties, because they offer high packing density, high screen brightness, high resolution and low scattering of light [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, most phosphors are prepared by conventional solidstate process, and the resulted samples contain irregular shape, broad size distribution. The appearance of new technology and new application, such as the ink-jet, plasma display panel (PDP) and field emission displays (FED), has brought higher demand for phosphor [1][2][3]. It has been reported that phosphor must have fine size, narrow size distribution, non-agglomeration mono-disperse spherical morphology for excellent luminescent properties, because they offer high packing density, high screen brightness, high resolution and low scattering of light [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Despite decades of use, however, some important aspects of the physics of phosphors remain topics of debate and investigation [1][2][3]. Depending on the material, this may include the structure of luminescence centers [3,4], the excitation and relaxation pathways [1,5], and/or the origin of the dead voltage [2,6]. (For most phosphors, no luminescence is observed when incident electrons' kinetic energy is below some threshold, which is usually orders of magnitude larger than the material's band gap.…”
mentioning
confidence: 99%
“…The luminescent efficiency of electron beams has been studied for a number of materials and beam properties [6,[16][17][18]. Luminescence can be expressed as the product of independent functions of the electron beam energy and beam current, with a linear dependence on current up to current densities far higher than pertains to our work [6,19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1͒ directly utilizes the electrons emitted from the cathode to bombard the CL phosphor coated on the anode and, thus, requires a much higher vacuum ͑Ͻ10 −6 torr͒. 8 In addition, due to its emission nature, the device usually produces pointlike light and needs a driving mechanism to scan the light for displaying purposes. Cathode ray tube is the typical example operating with this mechanism.…”
mentioning
confidence: 99%